Socialization of Stunting Prevention with Education to Improve Diet - Asriati Asriati; Natalia Paskawati Adimuntja; Zul Fikar Ahmad (ABDIMAS: Jurnal Pengabdian Masyarakat, 2022)
Elderly is an advanced stage of the life process decreasing the body's ability to adapt to the environment. Degenerative disease is a disease that occurs due to decreased organ function, including hypertension, rhematoid arthritis, stroke, diabetes mellitus. Various strategies are pursued to improve health status and reduce morbidity in the elderly. One of them is through physical activity that is in accordance with the physical condition of the elderly and is carried out regularly. In addition, increasing knowledge through counseling which aims to help the elderly make decisions and determine a healthy lifestyle. The purpose of this activity is to improve the quality of life of the elderly. The method used is by doing elderly exercise with pre and post blood pressure checks so that it can be seen the significance of the benefits of exercise. In addition, counseling was carried out using lecture, discussion and question and answer methods. The target audience for this community service program is the elderly (elderly) in the Poskesdes Village of Benteng who are physically categorized as doing sports / physical activity for the elderly. The results of this activity show that the effectiveness of elderly gymnastics has an effect on reducing blood pressure. And from counseling, the results of the evaluation show that the elderly understand and understand the concept of healthy elderly people related to the pandemic.